MANAJEMEN KUALITAS JASA PERAWATAN MOTOR DENGAN METODE SERVQUAL, QUALITY FUNCTION DEPLOYMENT DAN MODEL KANO - Risky Ramadhano; Anjar Priyono (Fakultas Bisnis UKDW, 2017)
The objective of this paper is to investigate the attributes of services at a scooter maintenance centreand how to improve the attributes. As many as 40 customers participated in this study to identify theattributes. The instrument was developed through a combination of literature review, interview focusgroup discussion. Unlike many other studies that assume a linear relationship between servicesattributes and customer satisfaction, this study considers the relationship as non-linear. For thisreason, this study does not only use Service Quality (SERVQUAL) Model but also Kano’s Modelwhich was combined with Quality Function Deployment. The analysis demonstrated that there were13 attributes required by customers of which 4, 5 and 4 were categorised as attractive, onedimensional and must-berespectively according to Kano’s Model. Managerial implication and futureresearch recommendation are also presented at the end of the paper.Keywords: Service quality, Kano’s Model, Quality Function Deployment, Service Performance, Voiceof Customer, House of Quality